Networking Method for the Structure of a Large Modular Deployable Space Antenna - Dake Tian; Xiaodong Fan; Junwei Zhang; Lu Jin; Rongqiang Liu; Yu Zhang (International Journal of Aerospace Engineering)
A high-precision networking method for a modular deployable antenna with ultramultiple modules is proposed to solve the problem of achieving an accurate formation of the structure of a large-aperture modular deployable space antenna. In accordance with the general requirements for the deployment surface of deployable antennas, the structure composition and deployment principle of a deployable antenna are analyzed, and the topological law of a hexagonal prism modular structure is expounded. On the basis of basic theories of differential geometry, analytical geometry, and robotics, the mathematical model of an envelope circle and that of its center are established. Then, a networking model of structure that includes 61 modules in the fully deployed state is established. Finally, the established model is verified via a numerical simulation method, and the influence law of structural parameters on networking characteristics is analyzed and studied. Simulation results show that the networking method can realize an accurate connection of multiple modules. The networking method for the structure of a modular deployable antenna proposed in this study can provide a reference for research on basic theory of a deployable antenna’s mechanism and related engineering applications.